SOEHARTO: CONTROVERSY AND ELIGIBILITY AS A NATIONAL HERO: Soeharto: Kontroversi dan kelayakan sebagai Pahlawan Nasional - Agustin, Yeni; Fahruddin (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This article discusses the controversy and feasibility regarding Soeharto's appointment as Indonesia's National Hero. Although Suharto is known for successfully advancing Indonesia's economy for 32 years, he was also involved in human rights violations, corruption, collusion and nepotism. The aim of writing this article is to examine the theoretical understanding of the issue of Soeharto's appointment as a national hero, the procedure for appointing a hero in Indonesia, as well as the public's views regarding the controversy and suitability of Soeharto to become a National Hero. Using qualitative research methods, this article explores the contributions and controversies surrounding Soeharto as well as the requirements for becoming a national hero. Various views from human rights activists and academics show the importance of moral integrity in honoring national heroes. Even though Suharto had significant contributions, his complex leadership legacy is best recognized as part of history without giving him the title of National Hero.